1997
DOI: 10.1136/bmj.314.7076.262
|View full text |Cite
|
Sign up to set email alerts
|

Relation between bed use, social deprivation, and overall bed availability in acute adult psychiatric units, and alternative residential options: a cross sectional survey, one day census data, and staff interviews

Abstract: Objective: To determine whether treatment with low dose aspirin and heparin leads to a higher rate of live births than that achieved with low dose aspirin alone in women with a history of recurrent miscarriage associated with phospholipid antibodies (or antiphospholipid antibodies), lupus anticoagulant, and cardiolipin antibodies (or anticardiolipin antibodies). Design: Randomised controlled trial. Setting: Specialist clinic for recurrent miscarriages. Subjects: 90 women (median age 33 (range 22-43)) with a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 11 publications
(7 reference statements)
3
46
0
1
Order By: Relevance
“…The pressure on beds appears to reflect a wider mismatch of provision and need [28]. This is in consonance with the fact that shortage of beds in acute psychiatric units is related to both social deprivation and the overall availability of acute beds [41,42]. It is reported that South Africa, Egypt, Ethiopia and Kenya have higher proportions of psychiatric beds, with the neuropsychiatric hospital, Aro Hospital having over 500 beds [24,39].…”
Section: Infrastructure Gapmentioning
confidence: 70%
See 2 more Smart Citations
“…The pressure on beds appears to reflect a wider mismatch of provision and need [28]. This is in consonance with the fact that shortage of beds in acute psychiatric units is related to both social deprivation and the overall availability of acute beds [41,42]. It is reported that South Africa, Egypt, Ethiopia and Kenya have higher proportions of psychiatric beds, with the neuropsychiatric hospital, Aro Hospital having over 500 beds [24,39].…”
Section: Infrastructure Gapmentioning
confidence: 70%
“…This decay has been going on for over a decade without adequate representation in learned journals, media houses and policy statements. In the study center, patients do not have privacy and there is concern that patients often do not have privacy, nor are they guaranteed the therapeutic and recreational facilities that are a necessary part of good care [41,42]. Women are not spared, as the situation depicted in this report that, there is clear evidence that women are particularly disadvantaged with regard to both privacy and safety [42].…”
Section: Infrastructure Gapmentioning
confidence: 71%
See 1 more Smart Citation
“…Their progress may also be hindered by the lack of opportunity to rehearse appropriate social roles and practical skills (Lelliottt & Quirk, 2004). The unacceptably high number of long-stay patients stuck on acute wards has been consistently reported and the associated shortcomings in community and longer stay in-patient provision have been highlighted (Kurian et al, 1994;Shepherd et al, 1997;Rowlands et al, 1998). The role of rehabilitation, whether in the hospital or in another placement, has largely been neglected (Holloway, 2005) during a decade that has seen national policy initiatives focus chiefly on the development of non-residential community services, notably assertive outreach and home treatment teams (Department of Health, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, admissions are often required to offer patients and others, particularly their carers, protection and respite. Frequently, hospital care may also prove the only alternative available when the prospect of living in the community is shattered by homelessness (Commander et al, 1997) and social deprivation (Shepherd et al, 1997).…”
mentioning
confidence: 99%